War in the modern world, 1990-2014 - Black, Jeremy, 1955-, author.
1 online resource (xi, 164 pages)
Keywords: "Looks at modern conflicts between 1990 and 2014 from a historical perspective. Argues that understanding non-Western developments is crucial if the potential of Western war-making is to be assessed accurately"--